The Outcast and the Rite: Stories of Landscape and Fear - Gildersleeve, Jessica (Australasian Journal of Victorian Studies, 2022)
Review of Melissa Edmundsen's edition of Helen de Guerry Simpson's "The Outcast and the Rite: Stories of Landscape and Fear, 1925-1938"